Impact of the gut microbiota on heat stroke rat mediated by Xuebijing metabolism. (June 2021) - Qiang, Wen; Xuan, He; Yu, Shao; Hailun, Peng; Yueli, Zhao; Zhiguo, Pan; Lei, Su
Abstract: The goal of the present study was to evaluate the fecal microbiome and serum metabolites in Xuebijing (XBJ)-injected rats after heat stroke using 16S rRNA gene sequencing and gas chromatography-mass spectrometry (GC-MS) metabolomics. Eighteen rats were divided into the control group (CON), heat stroke group (HS), and XBJ group. The 16S rRNA gene sequencing results revealed that the abundance of Bacteroidetes was overrepresented in the XBJ group compared to the HS group, while Actinobacteria was underrepresented. Metabolomic profiling showed that the pyrimidine metabolism pathway, pentose phosphate pathway, and glycerophospholipid metabolism pathway were upregulated in the XBJ group compared to the HS group. Taken together, these results demonstrated that heat stroke not only altered the gut microbiome community structure of rats but also greatly affected metabolic functions, leading to gut microbiome toxicity.